A Review of the Financial Value of Faecal Sludge Reuse in Low-Income Countries - Mallory, Adrian; Holm, Rochelle H.; Parker, Alison (MDPI, 2020)
Faecal sludge reuse could promote responsible waste management and alleviate resource shortages. However, for this reuse to be carried out at scale, it needs to be financially viable. This paper reviews the financial values of resource recovery from 112 data points from 43 publications from academic and grey literature. The results found 65% of the existing literature is projected rather than being based on observed data from products in practice, with limited studies providing actual experiences of revenue in practice. Some of the estimates of the potential value were ten times those observed in data from operating businesses. Reasons for this include pricing of products against unrealistic competitors, for example, pricing briquettes against diesel fuel, or di culties in marketing or regulation of products in practice. The most common form of reuse in practice is agricultural composting, which is also the lowest value product. Few cases were able to achieve more than $5/person/year from sludge reuse, therefore other drivers are needed to promote proper human waste disposal, including the health and dignity of citizens, but which are not easily monetised. Certification and recognition of product safety can improve the perception of value and products. Resource recovery has a limited role in the financial viability of providing Circular Economy sanitation in low-income countries. Instead, there is a need to focus on supportive policies and subsidies enabling the transition towards a Circular Economy supporting environmental quality, ecological health and human health.
Keywords: Agriculture; Economics; Sanitation; Waste Management